Multiple endocrine neoplasia - Thakker, R (2009)
Multiple endocrine neoplasia (MEN) is characterized by tumours involving two or more endocrine glands within a single patient. There are two major forms of MEN: type 1 (MEN1, Wermer's syndrome) and type 2 (MEN2, Sipple's syndrome). MEN1 is characterized by the combined occurrence of tumours in the parathyroids, pancreatic islet cells and anterior pituitary; MEN2 is characterized by the association of medullary thyroid carcinoma, phaeochromocytoma and parathyroid tumours. Non-endocrine tumours may also arise, for example lipomas, collagenomas and angiofibromas occur in MEN1, and mucosal neuromas in MEN2b. The MEN1 gene is on chromosome 11q13 and is a putative tumour suppressor gene that encodes a 610 amino acid protein, MENIN, which has roles in transcription regulation, genome stability and cell division. The MEN2 gene is on chromosome 10q11.2 and encodes a tyrosine kinase receptor. The MEN syndromes are uncommon, but because they are inherited as autosomal dominant disorders, the finding of MEN in a patient has important implications for other family members; first-degree relatives have a 50% risk of developing the disease. Thus, biochemical and genetic screening are important in patients with MEN syndromes and their families. Testing for MEN1 and MEN2 mutations is available through regional genetic laboratories. © 2009 Elsevier Ltd. All rights reserved.